Assessment of quantitative [18F]Sodium fluoride PET measures of knee subchondral bone perfusion and mineralization in osteoarthritic and healthy subjects. Issue 6 (June 2021) - Watkins, L.; MacKay, J.; Haddock, B.; Mazzoli, V.; Uhlrich, S.; Gold, G.; Kogan, F.
Summary: Objective: Molecular information derived from dynamic [ 18 F]sodium fluoride ([ 18 F]NaF) PET imaging holds promise as a quantitative marker of bone metabolism. The objective of this work was to evaluate physiological mechanisms of [ 18 F]NaF uptake in subchondral bone of individuals with and without knee osteoarthritis (OA). Methods: Eleven healthy volunteers and twenty OA subjects were included. Both knees of all subjects were scanned simultaneously using a 3T hybrid PET/MRI system. MRI MOAKS assessment was performed to score the presence and size of osteophytes, bone marrow lesions, and cartilage lesions. Subchondral bone kinetic parameters of bone perfusion (K1 ), tracer extraction fraction, and total tracer uptake into bone (Ki ) were evaluated using the Hawkins 3-compartment model. Measures were compared between structurally normal-appearing bone regions and those with structural findings. Results: Mean and maximum SUV and kinetic parameters Ki, K1, and extraction fraction were significantly different between Healthy subjects and subjects with OA. Between-group differences in metabolic parameters were observed both in regions where the OA group had degenerative changes as well as in regions that appeared structurally normal. Conclusions: Results suggest that bone metabolism is altered in OA subjects, including bone regions with and without structural findings, compared to healthy subjects. Kinetic parameters of [ 18 F]NaF uptake in subchondral bone show potential to quantitatively evaluate the role of bone physiology in OA initiation and progression. Objective measures of bone metabolism from [ 18 F]NaF PET imaging can complement assessments of structural abnormalities observed on MRI.